RESISTANCE TRAINING AND FITNESS CLASSES IN THE ELDERLY: A COMPARATIVE ANALYSIS THROUGH THE TEST GROUP OF LATIN AMERICAN DEVELOPMENT FOR MATURITY (LADM). (Fiep Bulletin - online, 2014)
The Resistance Training (RT) and classes Physical Fitness (CF) spaced, are the most applied to the elderly population due to its easy handling and control of variable factors relevant to the training; From this information, the concept worked TR and CF classes held at intervals, applied projects "Physical Fitness, Health and Strength" and "Polo Sport SEDUC / NEL" and a sample of the research within the elderly age 50 cut to 70 years, with the objective main analyze and compare the physical capabilities and autonomy of older people who do resistance training in the Laboratory of Health and resistance exercises (LERES) and seniors participating in the project Polo Sport SEDUC / NEL, the fitness classes at intervals, using as benchmark groups, the test group of Latin American Development to Maturity (LADM); specific objectives are to scan as a physical training influence on the performance of individual elderly in their daily tasks; analyze how resistance training and functional influence the functional capabilities of strength. Statistical data of the research were presented in tables and graphs and statistical analysis was performed using the Statistical Package SPSS 18.0 where it adopted the descriptive statistics (mean and standard deviation) for sample characterization, and inferential statistics through the Student t test for comparing the means of the variables between the different sample groups; Having highlighted the line of authors who defend the practice of TR, such as maintenance of lean body mass, increased bone mineral density, control of diseases such as hypertension, stroke, obesity, diabetes, etc., muscle strengthening seeking life extension and reduction of problems and obstacles imposed health and quality of life in excellent condition.
Keywords: Resistance Training; Fitness; Elderly; LADM.